2004
DOI: 10.1177/0022002704266148
|View full text |Cite
|
Sign up to set email alerts
|

The Limitations of Fair Division

Abstract: Mathematical procedures that promise an envy-free, equitable, and efficient solution to distributional conflicts have received widespread attention. Two fair-division mechanisms, adjusted Knaster and proportional Knaster, which are similar to the well-known adjusted-winner procedure, are compared with the less fair divide-and-choose mechanism. Results show that participants largely prefer the adjusted-Knaster procedure to the two alternatives. Adjusted Knaster, closely followed by proportional Knaster, also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…The experimenters then compare different division procedures according to various criteria, such as: perceived fairness, economic efficiency, etc. [23,46]. Other experiments test what desiderata are more important to the subjects when there is a conflict, e.g.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…The experimenters then compare different division procedures according to various criteria, such as: perceived fairness, economic efficiency, etc. [23,46]. Other experiments test what desiderata are more important to the subjects when there is a conflict, e.g.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…In particular, do users prefer the allocations generated by sophisticated and provably-fair procedures, to the allocations generated by simple and intuitive procedures? Schneider and Krämer (2004) compare the simple divide-and-choose procedure to the more sophisticated Adjusted-Knaster and Proportional-Knaster procedures, for allocating indivisible goods with monetary compensation. They find that, if the participants truthfully adhere to the protocol, then the sophisticated mechanisms perform better than divide-and-choose in terms of efficiency and fairness.…”
Section: Sophisticated Versus Simplementioning
confidence: 99%
“…The experimental literature on fair division (see for instance Daniel and Parco (2005) or Schneider and Kramer (2004)) has already shown that agents may not always reveal their information truthfully. The absence of a theoretical framework means thay cannot interpret these deviations from truthful behaviour.…”
Section: Related Literaturementioning
confidence: 99%
“…those that value their most preferred issue 350 or 400). 25 We also want to analyse the behaviour of subjects that value both issues equally and hence are indifferent between possible strategies. The way they play is relevant to our welfare analysis: only when they split their votes do they allow our simple mechanism to reach the ex-ante optimal incentive compatible allocation (i.e.…”
Section: The Case With Two Issuesmentioning
confidence: 99%